Endoscopic surveillance of Lynch syndrome at a highly specialized center in Sweden: An observational study of interval colorectal cancer and individual risk factors - Jamizadeh, Nigin; Walton Bernstedt, Sophie; Haxhijaj, Adrianna; Andreasson, Anna; Björk, Jan; Forsberg, Anna; Backman, Ann-Sofie (Frontiers in Oncology, 2023)
Introduction: Lynch syndrome (LS) is the most common hereditary cause of colorectal cancer (CRC). In order to detect CRCs amongst LS patients, regular colonoscopies are recommended. However, an international agreement on an optimal surveillance interval has not yet been reached. In addition, few studies have investigated factors that could potentially increase the CRC risk amongst LS patients. Aims: The primary aim was to describe the frequency of CRCs detected during endoscopic surveillance and to estimate the interval from a clean colonoscopy to CRC detection amongst LS patients. The secondary aim was to investigate individual risk factors, including sex, LS genotype, smoking, aspirin use and body mass index (BMI), on CRC risk amongst patients that develop CRC before and during surveillance. Material and Methods: Clinical data and colonoscopy findings from 366 LS patients’ 1437 surveillance colonoscopies were collected from medical records and patient protocols. Logistic regression and Fisher’s exact test were used to investigate associations between individual risk factors and CRC development. Mann-Whitney U test was used to compare the distribution of TNM stages of CRC detected before surveillance and after index. Results: CRC was detected in 80 patients before surveillance and in 28 patients during surveillance (10 at index and 18 after index). During the surveillance programme, CRC was detected within 24 months in 65% of the patients, and after 24 months within 35% of the patients. CRC was more common amongst men, previous and current smokers, and the odds of developing CRC also increased with an increasing BMI. CRCs were more often detected amongst MLH1 and MSH2 carriers during surveillance, compared to the other genotypes. Conclusions: We found that 35% of the CRC cases detected during surveillance were found after 24 months. MLH1 and MSH2 carriers were at higher risk of developing CRC during surveillance. Additionally, men, current or previous smokers, and patients with a higher BMI were at higher risk of developing CRC. Currently, LS patients are recommended a “one-size-fits-all” surveillance program. The results support the development of a risk-score whereby individual risk factors should be taken into consideration when deciding on an optimal surveillance interval.